EDUKASI DAUR ULANG SAMPAH ORGANIK MENJADI PUPUK KOMPOS DI KELURAHAN PASAR AMBACANG KECAMATAN KURANJI KOTA PADANG - Novia Wirna Putri; Septia Pristi Rahmah; Syafa Indah Tafsia; Valda Yasmina Putri (LPPM Universitas Andalas, 2022)
In 2019, the population of Padang City increased to 950,871 people, with waste generation of 624.24 tons/day. Research on solid waste in Indonesia shows that 80% of it is organic waste. If we are able to handle this waste problem properly, this organic waste can be processed into compost which is very useful for increasing soil fertility. The problems that exist today are that waste is still not managed properly, most of the people do not have the skills to process organic waste into something useful and economical, so that it can increase people's productivity in processing waste and improve their welfare. The purpose of this activity is to increase the knowledge of the people of Pasar Ambacang Village, Padang City regarding organic waste recycling as an effort to control environmental pollution and to improve community skills in recycling organic waste. The method of implementing the activities consists of the stages of planning activities, implementing and monitoring the evaluation of activities. The result of this activity is that there is an increase in participants' understanding of organic waste processing through the compost method by 31.7%. The community has been able to process organic waste at home using a composter. The community can also use the compost that has been made as plant fertilizer. With this activity, the community has contributed to reducing waste generation in the landfill and creating a healthy and clean environment.